Rational multivalency construction enables bactericidal effect amplification and dynamic biomaterial design - Xu Chen; Xinrui Li; Wenbo He; Miao Wang; Ang Gao; Liping Tong; Shun Guo; Huaiyu Wang; Guoqing Pan (The Innovation, 2023)
The multivalency of bioligands in living systems brings inspiration for not only the discovery of biological mechanisms but also the design of extracellular matrix (ECM)-mimicking biomaterials. However, designing controllable multivalency construction strategies is still challenging. Herein, we synthesized a series of well-defined multivalent antimicrobial peptide polymers (mAMPs) by clicking ligand molecules onto polymers prepared by reversible addition-fragmentation chain transfer polymerization. The multiple cationic ligands in the mAMPs could enhance the local disturbance of the anionic phospholipid layer of the bacterial membrane through multivalent binding, leading to amplification of the bactericidal effect. In addition to multivalency-enhanced antibacterial activity, mAMPs also enable multivalency-assisted hydrogel fabrication with an ECM-like dynamic structure. The resultant hydrogel with self-healing and injectable properties could be successfully employed as an antibacterial biomaterial scaffold to treat infected skin wounds. The multivalency construction strategy presented in this work provides new ideas for the biomimetic design of highly active and dynamic biomaterials for tissue repair and regeneration.